Predictors of Stress in College Students - Saleh, Dalia; Camart, Nathalie; Romo, Lucia (Frontiers in Psychology, 2017)
University students often face different stressful situations and preoccupations: the first contact with the university, the freedom of schedule organization, the selection of their master's degree, very selective fields, etc. The purpose of this study is to evaluate a model of vulnerability to stress in French college students. Stress factors were evaluated by a battery of six scales that was accessible online during 3 months. A total of 483 students, aged between 18 and 24 years (Mean = 20.23, standard deviation = 1.99), was included in the study. The results showed that 72.9, 86.3, and 79.3% of them were suffering from psychological distress, anxiety and depressive symptoms, respectively. More than half the sample was also suffering from low self-esteem (57.6%), little optimism (56.7%), and a low sense of self-efficacy (62.7%). Regression analyses revealed that life satisfaction, self-esteem, optimism, self-efficacy and psychological distress were the most important predictors of stress. These findings allow us to better understand stress-vulnerability factors in students and drive us to substantially consider them in prevention programs.